Identification of QTLs for internode length and diameter associated with lodging resistance in rice - Lin, Qiuyun; Gan, Ping; Zhou, Yujie; Lin, Yuehui; Xie, Zhenyu; Hu, Wei (Frontiers in Plant Science, 2025)
IntroductionLodging is a significant challenge in rice production, particularly for high-yielding cultivars. Previous research has shown that stem characteristics, such as internode length and diameter, are key determinants of lodging resistance. However, the genetic mechanisms controlling these traits remain poorly understood.MethodsTo investigate the genetic basis of lodging-related stem traits, a recombinant inbred line (RIL) population was developed from a cross between Zhenshan 97 and C309, two rice varieties with contrasting stem architectures. A high-density genetic linkage map was constructed using 3,307 bin markers generated by next-generation sequencing. Comprehensive phenotypic analysis was conducted for heading date, internode length, and diameter.ResultsA total of 54 quantitative trait loci (QTLs) were identified across the genome. Importantly, 15 pleiotropic QTLs were detected, each affecting multiple internode-related traits. These pleiotropic loci include well-known functional genes such as SCM2 and Gn1a, as well as several novel loci potentially involved in regulating stem strength and lodging resistance. Additionally, RNA-Seq analysis was performed to identify candidate genes associated with these traits. Among the 1,263 expressed genes within the 15 pleiotropic QTL regions, 183 differentially expressed genes were identified. LOC_Os06g11130 was highlighted as a key gene for further investigation. Haplotype analysis and linkage disequilibrium analysis revealed significant haplotype variation in LOC_Os06g11130, further confirming its potential role in lodging resistance.DiscusssionThis study enhances our understanding of the genetic architecture of internode traits associated with lodging resistance in rice. The identification of pleiotropic and major-effect QTLs provides valuable genetic resources for marker-assisted selection and genomic breeding, with the potential to improve lodging resistance in high-yielding rice cultivars. These findings contribute to the development of rice varieties that balance high yield potential with enhanced lodging resistance.